Investigation of the H-bond-mediated aglycone delivery reaction in application to the synthesis of β-glucosides. (December 2018) - Mannino, Michael P.; Yasomanee, Jagodige P.; Demchenko, Alexei V.
Abstract: In an attempt to refine the H-bond-mediated Aglycone Delivery (HAD) glycosylation reaction reported herein is the synthesis of β-glucosides using an ethylthio glucoside donor equipped with the remote 6- O -picoloyl substituent. Upon examining various aliphatic, aromatic, and carbohydrate acceptors, it was determined that both electronic and steric factors may greatly affect the stereoselectivity of the HAD reaction with this donor. Graphical abstract: Highlights: The HAD-capable glycosyl donor showed a great variation of the results depending on the nature of acceptors used. Primary acceptors, both carbohydrate and aliphatic alcohols afforded the glycosylation products with complete β-selectivity. Both steric and electronic factors may affect the stereoselectivity of HAD reaction for the synthesis of β-glucosides.